Taking on or leaving behind a doctoral identity - Cyster, Grant Alexander (Rhodes University, 2026)
This doctoral study aimed to examine supervision- and institutional-related issues of attrition in doctoral education in South Africa through elevating the voices of former doctoral candidates who withdrew from their programme of study. It accomplished this by conducting a narrative study on the doctoral education experiences of six former candidates who terminated their studies at a South African university. The study used a narrative research methodology and employed the theoretical framework of Pierre Bourdieu’s field theory. The study participants were identified using methods of broad surveying via social media platforms, and a ‘snowball’ word-of-mouth approach within the context of existing academic and professional peer networks. The researcher conducted narrative and semi-structured interviews (referred to in the study as conversations) with the six participants as the study’s primary source of data. Additional data were obtained from an examination of the higher degrees guides of some South African universities, as well as an analysis of the South African Doctoral Degrees National Review 2022 document. A combination of narrative, thematic and document analysis was undertaken in working with the relevant data, using field theory to extract points of meaning and significance from the data. Field theory allowed the researcher to explore and illuminate important issues related to doctoral education and attrition. These issues include how supervision practices and support structures impact candidates’ identity and chances for success; the accumulation, preservation and impact of power in the field; and, the often hidden and implicit ‘rules of the game’ that influence who is advantaged and disenfranchised within the field based on the forms and volumes of capital they possess. Specifically, who gets to determine which capitals in the field are valued and which are not, and how this impacts upon progress in doctoral study. The study determined that attrition in doctoral education is complex and multi-faceted and can have long-lasting academic, identity and emotional effects on doctoral candidates. Furthermore, misinformed, mismatched and unmet expectations in the field potentially result in a myriad challenges in the doctoral supervision relationship and in doctoral education more broadly. The findings of the study may help universities consider more carefully candidate and supervisor preparedness and fit; may help doctoral educators critique and change doctoral and supervisor training and development, and update institutional support mechanisms; and help us understand better the production, protection and perpetuation of power in doctoral supervision.
analysing narratives of attrition in South African doctoral education
Keywords: Narrative inquiry (Research method) (http://id.loc.gov/authorities/subjects/sh2006004688); Discourse analysis, Narrative (http://id.loc.gov/authorities/subjects/sh85038364); Universities and colleges--Graduate work (http://id.loc.gov/authorities/subjects/sh85141124); Field theory (Linguistics) (http://id.loc.gov/authorities/subjects/sh85048116); Doctoral education (https://www.wikidata.org/wiki/Q98939020); Drop-out rate (https://www.wikidata.org/wiki/Q3981411)